Correlations between psychomotor abilities and selected personality variables in rowers - Wilczynska, D. (Baltic Journal of Health and Physical Activity, 2016)
Background: The purpose of this study was to present possibilities of using computer tests in the assessment of chosen cognitive skills and an analysis of correlations between the mentioned variables and the level of optimism, self-efficacy, coping strategies, anxiety and perceived stress in Polish national team rowers.